ARAH PEMBAHARUAN HUKUM NASIONAL DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Suratno, Ujang (Universitas Wiralodra, 2019)
Indonesia has some varieties of ethnic groups that are rich in diversity of intellectual property, there are so many products produced by society. The society creations especially created by the community are assorted, one of them is Paoman Batik. Thre are two kinds of Paoman Batik, those are contemporary and traditional, which is distinguished by its motives, processes, creators. The Paoman Traditional Batik is well-known to the public than contemporary. This research has supported the creators or copyright holders to get higher benefits, both the benefits of moral and economic rights. The main problem is, first, is the current intellectual property rights regime able to provide the foundation for the protection of Paoman Traditional Batik? Second, is the UNESCO's determination that stated if batik is a world heritage, non-object from Indonesia, can be used as the foundation to charge the economic rights of Paoman Traditional Batik? Third, is it possible for Traditional Batik, including Paoman Traditional Batik, to be carried out through other regimes, in addition to the intellectual property regime? Fourth, how is the effect of Paoman Traditional Batik Registered at the Directorate General of Intellectual Property of Indonesia on the Progress of Indramayu society? The research method used is descriptive specification, by using juridical empirical approach, which focus on secondary research consisting of legal materials, both primary, secondary and tertiary. However it is supported by primary data generated from field research through in-depth interview and survey techniques. The analysis used is descriptive analysis. The results of the study show that intellectual property rights that is copyright cannot be made as the foundation of protection against the creation of society that have traditional and communal motives, including the Paoman Tradsional Batik. The establishment of Batik by UNESCO as a non-object world heritage from Indonesia has increased the moral rights of Indonesia, but it also cannot be established as the foundation for restoring economic rights when there is a misappropriation. Another alternative to intellectual property is through the Sui Generis regime, which specifically addresses the protection of community rights, including intellectual property rights.